OTA high pass filter-based multiphase sinusoidal oscillator - Thongdit, Preecha; Kunto, Terdsak; Prommee, Pipat (My University, 2015)
This paper proposes a new approach to implement a multiphase sinusoidal oscillator using loop-back of n-cascaded high-pass filters form. Two basic CMOS Multiple Outputs Operational Transconductance Amplifier (MOOTA) and grounded capacitors are constructed as a current-mode high-pass filter. Gain and frequency response of high-pass filter can be independently tuned through the particular bias current. It is, therefore, orthogonally of oscillation condition and frequency oscillation is obtained through bias currents of each OTA. Multiphase sinusoidal current output and voltage output can be obtained with equally space in phase of 360/n degree. Third-order high-pass filter has been raised to confirm the theoretical agreement. Low-harmonic distortion of achieved sinusoidal output less than 0.75% is obtained. The performances are carried out by PSpice for confirm its attractive characteristics.
Keywords: High-pass filter; Multiphase Oscillator; OTA